Character Values of Independence Hadratussyekh K.H. M. Hasyim Asy'ari - Johan Setiawan (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This study aims to explain: (1) The background of the life of Hadratussyekh K.H. M. Hasyim Asy'ari in the trajectory of Indonesian history. (2) The entrepreneurial character values contained in Hadratussyekh K.H. M. Hasyim Ash'ari. This research is historical research with steps, namely: heuristics, verification, interpretation, and historiography. This study uses document sources consisting of primary and secondary sources. The results showed that: (1) Hadratussyekh K.H. M. Hasyim Asy'ari was born and grew up in an environment that has high religiosity, making him have good character and morals. (2) The entrepreneurial character values of Hadratussyekh K.H. M. Hasyim Asy'ari who can emulate one of which is the value of the character of independence.